Prediction of relationship between angular velocity to the pitch line velocity (ω/v) on tensile strength of friction stir welded AA2014-T6 Aluminium alloy joints - Rajendran C (Elsevier, 2021)
High-strength aluminum alloys, such as the 7xxx and 2xxx series, are well suited for components and structures. It includes a greater strength ratio and is typically used in fabrication of fuselage and wing skins. AA2014 is difficult to join using a fusion welding process because of its high thermal conductivity, oxidation behavior and low melting point, which can easily lead to burn through and porosity. To alleviate these difficulties, Friction Stir Welding (FSW), a solid-state welding process was deployed. The tool and process parameters are the most vital part in material flow in FSW. The sound welded joints aligned towards the material flow in the weld region under sufficient strain rate. Of which, the angular velocity and pitch line velocity play crucial role in heat generation during the FSW cycle. The effect of angular velocity to pitch line velocity(ω/v) on the tensile properties of the aluminum AA2014 friction stir welded joints was analyzed. To make the joints, five tools with varying shoulder diameter (4 mm, 5 mm, 6 mm, 7 mm, and 8 mm) were used. Microstructure was performed to correlate strength properties of FSW joints. It is found that the joint produced with a ω/vratio of 0.33 exhibited greater tensile properties compared to other joints. It was due to the balanced material flow, development of fine grains and uniform spread of second phase particle in the stir zone.